APPLICATION EFFICIENCY OF MONTELUKAST AMONG CHILDREN SUFFERING FROM BRONCHIAL ASTHMA - A.K. Gevorkyan; E.A. Galeeva (Педиатрическая фармакология, 2008)
The article provides the results of montelukast efficiency depending on bronchial asthma severity level and the duration of a disease; the assessment of functional figures dynamics, disease pattern before and after the treatment with montelukast and the possibility of its application as mono therapy to achieve long term disease remission and asthma symptoms control.Key words: bronchial asthma, montelukast, children.